The Effect of Tax Avoidance Aggressiveness and Financial Distress on Audit Report Lag with Firm Size as A Moderating Variable - Lidia Putri Anjani; Rahmat Mulyana Dali; Verni Asvariwangi (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the effect of tax avoidance aggressiveness and financial distress on audit report lag with firm size as a moderating variable. Audit report lag reflects the duration required to complete the audit process of financial statements and may affect the timeliness of financial reporting. This study used a quantitative method with secondary data obtained from annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange during 2019–2024. The sampling technique used purposive sampling and resulted in 22 companies with 108 observation data after outlier elimination. Data analysis was conducted using panel data regression with the assistance of EViews 13. The results indicate that tax avoidance aggressiveness has a positive and significant effect on audit report lag, while financial distress does not significantly affect audit report lag. Furthermore, firm size is able to moderate the effect of tax avoidance aggressiveness on audit report lag, but is unable to moderate the effect of financial distress on audit report lag. These findings indicate that aggressive tax avoidance practices increase audit complexity and extend the audit completion period.